2021
DOI: 10.1088/2053-1591/abe520
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue life prediction of magneto-rheological elastomers in magnetic field

Abstract: Fatigue life is one of the most important characteristics of materials. Predicting fatigue life in magnetorheological elastomer (MRE) under combined and repetitive loads is an unavoidable step to increase the safety coefficient of MREs. In this study, high-temperature vulcanization silicon rubber (HTVSR) based MREs were fabricated by incorporating the different soft carbonyl iron particles (CIP) that samples with 10%, 20%, and 30% of CIP volume were made. Fatigue behavior of MRE under the combination of compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Soft CI magnetic particle (d50 ¼ 6.0-7.0 mm, CS grade, supplied by BASF) is chosen in an approximate size of 6 to 7 mm because it has excellent soft magnetic properties and high saturation magnetization. The used fabrication procedure was described in a previous paper 19 for isotropic samples.…”
Section: Mre Sample Fabricationmentioning
confidence: 99%
See 2 more Smart Citations
“…Soft CI magnetic particle (d50 ¼ 6.0-7.0 mm, CS grade, supplied by BASF) is chosen in an approximate size of 6 to 7 mm because it has excellent soft magnetic properties and high saturation magnetization. The used fabrication procedure was described in a previous paper 19 for isotropic samples.…”
Section: Mre Sample Fabricationmentioning
confidence: 99%
“…The MRE impedance properties and the storage modulus increased under magnetic fields. Hosseini et al 19 presented the relationship between maximum energy density function and fatigue life for MREs containing 0, 10, 20, and 30 vol% of CIP in the presence and absence of the magnetic field. They investigated a combination of multi-axial compression-tension and torsional forces in fixed magnetic fields for fatigue life of MREs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 CI particles are highly preferred as they possess several advantageous properties, including high saturation magnetization, ease of magnetization and demagnetization, and the absence of magnetic hysteresis. Hosseini et al 6 examined the impact of varying volumes of carbonyl iron particles (CIP) on the fatigue life of MREs. The findings revealed that, at the same volume percentage of CIP, the dissipated energy was reduced in the presence of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…The use of these elastomers is always defined by their characteristic physicochemical properties, including high elasticity, flexibility, chemical resistance, and impact resistance, which are essential for many applications. On the other hand, typical examples of magnetic fillers include carbonyl iron (CI), 11,12,14,16 Fe, 17 CoFe 2 O 4 , 18 Ni, 19 Co, 13 and FeCo 3 20 particles. These active fillers based on soft or hard particles with nano‐ or micrometer‐sized must be carefully selected to obtain an adequate combination of MRE properties.…”
Section: Introductionmentioning
confidence: 99%